Content validation of an assessment tool to measure lean deployment based on the Toyota Production System and Toyota Way. (2018) - Loyd, Nicholas
This research focused on the development and content validity of an assessment tool to measure an organisation's level of lean deployment based on the Toyota Production System-Toyota Way model. Survey items were developed from a first-person perspective in order to capture an assessment of an organisation's culture from the inside out. The survey was subjected to subject matter expert review for qualitative content validation. Quantitative methods such as parametric and non-parametric exploratory factor analysis and reliability analysis were used to evaluate and modify the structure of the assessment tool. The result of this research was an assessment tool that exhibits strong content validity and consists of 30 items that measure the five constructs of the Toyota Production System and the Toyota way culture. The finalised survey can now be subjected to further statistical analysis to test for overall construct validity.